Persisting social participation restrictions among former Buruli ulcer patients in Ghana and Benin. - Janine de Zeeuw; Till F Omansen; Marlies Douwstra; Yves T Barogui; Chantal Agossadou; Ghislain E Sopoh; Richard O Phillips; Christian Johnson; K Mohammed Abass; Paul Saunderson; Pieter U Dijkstra; Tjip S van der Werf; et al. (PLoS Neglected Tropical Diseases, 2014)
Buruli ulcer may induce severe disabilities impacting on a person's well-being and quality of life. Information about long-term disabilities and participation restrictions is scanty. The objective of this study was to gain insight into participation restrictions among former Buruli ulcer patients in Ghana and Benin.In this cross-sectional study, former Buruli ulcer patients were interviewed using the Participation Scale, the Buruli Ulcer Functional Limitation Score to measure functional limitations, and the Explanatory Model Interview Catalogue to measure perceived stigma. Healthy community controls were also interviewed using the Participation Scale. Trained native interviewers conducted the interviews. Former Buruli ulcer patients were eligible for inclusion if they had been treated between 2005 and 2011, had ended treatment at least 3 months before the interview, and were at least 15 years of age.In total, 143 former Buruli ulcer patients and 106 community controls from Ghana and Benin were included in the study. Participation restrictions were experienced by 67 former patients (median score, 30, IQR; 23;43) while 76 participated in social life without problems (median score 5, IQR; 2;9). Most restrictions encountered related to employment. Linear regression showed being female, perceived stigma, functional limitations, and larger lesions (category II) as predictors of more participation restrictions.Persisting participation restrictions were experienced by former BU patients in Ghana and Benin. Most important predictors of participation restrictions were being female, perceived stigma, functional limitations and larger lesions.